A materialist perspective for art teaching: research issues (Revista de Ensino em Artes, Moda e Design, 2024)
The article highlights the epistemological and methodological principles of historical-dialectical materialism (MARX, 2010) and its approach to the teaching of Visual Arts based on the contributions of Historical-Critical Pedagogy (SAVIANI, 2012; 2020). To this end, we will first discuss the issue of the Marxist method and its interpretation in art research (LUKÁCS, 2018; VÁZQUEZ, 1978).   Next, we will approach the teaching of Art in the capitalist school considering the need for an education that counteracts alienation and fulfills the function of transmitting systematized knowledge to new generations. In this aspect, Historical-Critical Pedagogy presents itself as a revolutionary pedagogical perspective by reaffirming the importance of school education for the formation of class consciousness and a condition for human emancipation. In this aspect, Historical-Critical Pedagogy presents itself as a revolutionary pedagogical perspective by reaffirming the importance of school education for the formation of class consciousness and a condition for human emancipation. Finally, we conclude that establishing a dialogue between the theoretical contribution of Marxism and the teaching of Visual Arts implies assuming a political and pedagogical posture committed to the development of humanity in its richest formative possibilities.
Keywords: marxist method; research in art; historical-critical pedagogy; art teaching